Increased Non-switched Memory B Cells are Associated with Plasmablasts, Serum IL-6 Levels and Renal Functional Impairments in IgAN Patients. (17th February 2020) - Si, Rui; Zhao, Pingwei; Yu, Zhenxiang; Qu, Zhihui; Sun, Weixia; Li, Tao; Jiang, Yanfang
ABSTRACT: Background : Circulating B cells are crucial for the pathogenesis of IgA nephropathy (IgAN). This study aimed at investigating the relationship between frequency of different subsets of circulating B cells and clinical measures in IgAN patients. Methods : The percentages of different subsets of circulating B cells in 23 IgAN patients and 14 healthy controls (HC) were determined by flow cytometry. Their serum IL-6 levels were measured by Cytometric Bead Array (CBA). Clinical parameters in five patients were measured before and after treatment for 8–12 weeks. The potential relationship between variants was analyzed. Results : In comparison with the HC, the frequency of CD3-CD19+ CD27+ IgD+IgM+ non-switched memory B cells ( P = .0038) and CD3-CD19+ CD27hiCD38hi plasmablasts ( P = .0467) and serum IL-6 ( P = .0392) levels significantly increased in IgAN patients. The percentages of non-switched memory B cells were positively correlated with plasmablasts (R = 0.5781, P = .0039) and serum IL-6 levels (R = 0.6663, P = .0005) in the patients. The percentages of non-switched memory B cells (R = 0.8399, P < .0001), plasmablasts (R = 0.4486, P = .0318) and the levels of serum IL-6 (R = 0.5461, P = .0070) were positively correlated with the values of 24-h urine proteins in IgAN patients. The serum levels of IL-6 were negatively correlated with the eGFR values. Following standard treatment, the frequency of non-switched memory B cells and plasmablasts and the levels of 24-h urine proteins ( P = .0317, P = .0079, P < .05) significantly decreased in IgAN patients. Conclusions : Abnormally higher frequency of non-switched memory B cells and plasmablasts may contribute to the pathogenesis of IgAN and be potential biomarkers for IgAN.